Characterization of Mesenchymal Stromal Cells after Serum Starvation for Extracellular Vesicle Production - Anna Lia Asti; Stefania Croce; Chiara Valsecchi; Elisa Lenta; Maria Antonietta Grignano; Marilena Gregorini; Adriana Carolei; Patrizia Comoli; Marco Zecca; Maria Antonietta Avanzini; Teresa Rampino (Applied Sciences, 2024)
It has been demonstrated that mesenchymal stromal cells (MSCs) act by releasing bioactive molecules, among these are extracellular vesicles (EVs). The MSC-EVs are considered a convenient alternative to cell therapy, showing several functional characteristics of their origin cells. EVs can be collected from conditioned in vitro cultured MSCs. Different processes have been developed to induce in vitro EV release, and these approaches have been demonstrated to also influence MSC potentialities. This study aimed to investigate the effect of serum starvation on MSC characteristics. The morphology, phenotype, differentiation capacity, immunomodulatory ability, and metabolic state were maintained by MSCs cultured under starvation. To evaluate basic ultrastructural characteristics of cells and EVs, Transmission Electron Microscopy (TEM) analysis was performed on MSCs after 12, 24, and 48 h starvation, demonstrating that 24 h starvation was the best time for MSC structure preservation. Further studies are needed to support the hypothesis that MSCs after starvation could still be considered as therapeutic agents.